Environmental and Legal Regulation of the Handling of Chemicals - KUDERINA, Assiya; KUDERIN, Ilyas; BEKEZHANOV, Dauren; AITIMOV, Bolat; NURBEK, Dana; AMREEVA, Indira (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
The implementation of a set of measures aimed at consistently reducing the negative impact of hazardous chemical factors on the population and the environment to an acceptable level of risk provides for the development and analysis of the experience of the European Union and its member States in the field of chemical management, as well as the development of recommendations for improving legislation and other regulatory legal acts on environmental protection from chemical pollution. To this end, the article presents the rationale and conceptual approaches to the formation of legislation in the field of chemical safety within the framework of state policy. The most important aspect in the formation of legislation is the global nature of chemical safety problems, in this connection, the article points to the need to bring the law in this area closer to partners in economic cooperation and integration. Taking into account the focus of future laws on reducing the level of negative impact of hazardous chemicals on the population and the environment, the legal and political consequences of their implementation are outlined.